Hubungan Pekerjaan, Paritas dan Jarak Tempuh dengan Kelengkapan Imunisasi Dasar Pada Balita Usia > 12 Bulan Sampai 5 Tahun di UPTD Puskesmas Tanjung Agung Kecamatan Baturaja Barat Kabupaten Ogan Komering Ulu (OKU) Tahun 2022 - Yesi Astrea; Ahmad Arif; Dewi Ciselia; Chairuna Chairuna (Universitas Batanghari Jambi, 2023)
One of the efforts to reduce morbidity and mortality in infants and toddlers is immunization. At the beginning of a baby's life is very susceptible to disease, if the baby is exposed to the disease it will cause physical, mental, disability, and cause death. Immunization is a promotive and preventive effort in preventing disease transmission in infants and toddlers. According to the World Health Organization (WHO) in 2018 it was stated that 86% of children under the age of 5 years globally had been immunized with 3 doses of Diphtheria, Tetanus and Pertussis (DPT3) and 1 dose of measles vaccine. They say that the number of children who are paralyzed due to polio has decreased by 99.9% worldwide. This study aims to determine the relationship between employment, parity and distance traveled with basic immunization completeness in children aged > 12 months to 5 years at the UPTD Puskesmas Tanjung Agung, Baturaja District. West Ogan Komering Ulu (OKU) Regency in 2022. The method in this study used a cross sectional with a population of 389 respondents and a sample of 79 respondents using a systematic random sampling technique. Data analysis used chi square statistical test with p value value (0.05). The results of this study were the relationship between occupation and completeness of basic immunization for children under five (p value = 0.003), parity relationship with completeness of basic immunization (p value = 0.04), while the relationship between distance traveled and completeness of basic immunization (p value = 0.001). Midwives are expected to further improve services, education for better evacuation so that basic immunization can be achieved even more in the Tanjung Agung Health Center Work Area.